The ragpicker king - Clare, Cassandra (Clare, Cassandra. Chronicles of Castellane, 2025)
Kel Saren, body double to Prince Conor, and Lin Caster, a healer with dangerous powers, navigate a web of royal conspiracies, criminal underworlds, and dark magic in Castellane, where their choices between love, loyalty, and betrayal could cost them everything, including their lives.